Poison [compact disc, unabridged] : a novel - Lescroart, John T. (Lescroart, John T. Dismas Hardy., 2018)
From the master of the legal thriller, John Lescroart, comes a dramatic family drama in which attorney Dismas Hardy is called on to defend a former client against the accusation of murder.